Influence of Simulators and Determinant Factors in the Virtual Baccalaureate (Docentes 2.0 Journal, 2021)
Technological development have changed the ways of work in the industry, demanding new skills from just graduated professionals. Currently in Mexico there is a great demand for qualified professionals with technical careers that the universities have not been able to cover, derived from the lack of training of students in these areas. This trend will continue to grow in the professional world in the coming years. The virtual laboratories and simulators are a means so that, through these spaces, it is possible to spread those convergent lines and show virtual education in disruptive educational models. It is considered that these laboratories will allow promoting through educational programs the vocation of high school students towards STEAM disciplines. It is important to highlight that with this research a methodology is derived that addresses the need to give academic continuity to the subjects with a practical approach in the context of the pandemic or that are by their nature are taught online.
Keywords: Innovation; Education; fab lab; simulators